Public Administrative Institutions in Vietnam: Current Situation and Reform Directions - Giao, Vu Cong (VNU Journal of Science: Legal Studies; Vol 41 No 4, 2025)
This article offers a comprehensive analysis of Vietnam’s administrative institutions, which constitute a central pillar in the country's public institutional framework and national governance structure. Adopting an institutionalist approach, the paper delineates the concept, structure, and functions of administrative institutions in the Vietnamese context. It identifies five core components: the system of administrative law, organizational structure of the bureaucracy, administrative procedures, public officials and civil service, and enforcement mechanisms. The article provides a critical assessment of the current status of administrative institutions in Vietnam, revealing significant shortcomings such as legal overlap, bureaucratic redundancy, procedural complexity, uneven quality of civil servants, and superficial oversight. It proposes an integrated and cross-sectoral reform framework to develop a more integrity-based, transparent, effective, and citizen-oriented administrative system. The study argues that reforming administrative institutions constitutes not only a technical imperative but also a strategic requirement for building a socialist rule-of-law state in Vietnam.